The Plastic Extension of a Chain of Rings Due to Axial Impact Load - J. F. Silva Gomes (1978)
The plastic response of a chain of circular rings due to an axial tensile impact load was investigated both experimentally and in part, analytically. Chains were built-up from circular aluminium rings and subjected to axial impact loading at one end. High-speed photography was employed to record the development of the deformation process. It was found that plastic collapse was progressively transmitted to neighbouring rings in the manner of a plastic wave. To investigate the situation analytically, a simplified approach was adopted which assumed rigid-perfectly plastic behaviour of the ring material and arrived at an equation of the same form as the classical one-dimensional elastic wave equation.